Stereoselective cardiovascular toxicity of difenoconazole stereoisomers in zebrafish larvae (Danio rerio) through thyroid hormone disruption - Jiansheng Zhu; Chunlan Liu; Jingyu Wang; Li Zou; Ju Dong; Mingtao Huang (Ecotoxicology and Environmental Safety)
Difenoconazole (DIF) is a typical chiral triazole fungicide extensively detected in the environment. This study aimed to explore the stereoselective cardiovascular toxicity of DIF and its four stereoisomers (2S,4S-, 2S,4R-, 2 R,4R-, and 2 R,4S-DIF) in zebrafish. Zebrafish embryos were exposed to DIF and its isomers at environmentally relevant concentrations (0.3, 0.6 and 1.2 mg/L) from 4 to 96 hours post fertilization (hpf) and cardiovascular development was systematically evaluated. Our results revealed that Rac-DIF, 2S,4S-DIF and 2 R,4R-DIF significantly decreased the survival rate, hatching rate and body length, and increased the malformation rate at 96 hpf. DIF isomers mainly produced severe stereoselective cardiovascular defects, manifesting as bradycardia, abnormal cardiovascular structure, intersegmental vessel defects, and altered expression of cardiovascular-related genes. Notably, 2 R,4R-DIF displayed the strongest cardiovascular toxicity, followed by 2S,4S-DIF and Rac-DIF. Transcriptome analysis showed that 2 R,4R-DIF and 2S,4S-DIF affected the thyroid hormone signaling pathway, which was validated by altered thyroid hormone levels and hypothalamus-pituitary-thyroid axis-related gene expression. Molecular docking indicated that 2 R,4R-DIF had the strongest binding to the active pockets of zebrafish thyroid hormone receptor β, followed by 2S,4S-DIF, 2S,4R-DIF and 2 R,4S-DIF. Fascinatingly, these adverse outcomes were partially recovered after T3 supplementation, indicating the importance of thyroid disruption in DIF isomers-induced stereoselective cardiovascular toxicity. Overall, this study revealed that DIF and its isomers induced stereoselective developmental and cardiovascular toxicity (ranked as 2 R,4R-DIF > 2S,4S-DIF > Rac-DIF > 2S,4R-DIF ≈ 2 R,4S-DIF) through thyroid hormone disruption, providing favorable information on the environmental risks of chiral DIF in aquatic organisms.